Migrant youth push back. Virtual friendships and everyday resistance in the digital sphere - Anna De Fina (Trabalhos em Linguística Aplicada, 2021)
Resistance has proven to be a hard concept to define. Debates about resistance in the sociological and sociolinguistic literature cover many aspects: from the degree to which resistance can be seen as related to established social groups (see Rampton 1996), to the level of agentivity and intention that is required for an action to be regarded as resistant, to the type of social behavior that qualifies. Thus, while some see resistance as based on actions, others see it as based on cultural appropriation (Hall and Jefferson 1976).  In their comprehensive review of literature on the topic, Hollander and Einwohner (2004) conclude that resistance can be seen as consisting of action and opposition. In this paper, I analyze resistance from the point of view of opposition to ideas, social situations, institutional actions and processes that result or may result in discrimination or stereotyping of specific social groups, as negotiated in the digital sphere by migrant and non-migrant youth belonging to a school-based community. Indeed, it has been argued (Chiluwa 2012, Chibuwe & Ureke 2016) that digital environments constitute ideal arenas for the development of resistance thanks to their wide reach and their ability to mobilize people around common themes. However, much of the research in this area has targeted organized resistance fueled by political or ethnic groups. In this paper I argue that resistance is an emerging process that does not necessarily stem within political contexts or from open choice, but can develop within interactional exchanges focused on everyday life events.  Thus, what I am interested in here is in how spontaneous acts and discourses of resistance emerge in the everyday exchanges of a diverse community that was not born around a particular social or political agenda.  For this paper, I will examine exchanges that happen on the Facebook page of one of the members of the community. I will show how resistance takes many forms: from irony and jokes to the raising of serious topics, to the dissemination of information and through different discourse genres: from storytelling to the posting of pictures.